Antimicrobial Stewardship Facetime: Comparison of Two Rounding Models at a Tertiary Medical Center. (4th October 2017) - Yang, Haoshu; Smith, Ethan; Marks, Gregory; Ochner, Margaret; Watson, Richard; Krishna, Sneha; Tran, Hai; Shane, Rita; Murthy, Rekha; Grein, Jonathan
Abstract: Background: As an 886-bed tertiary care hospital with both teaching and private physician groups, Cedars-Sinai Medical Center has a unique opportunity to incorporate antimicrobial stewardship pharmacist (ASP) rounds with both a general medicine teaching service (TS) as well as a non-teaching hospitalist group (NTH). The impact of ASP rounds on antimicrobial (ABX) utilization and notable differences in clinical outcomes associated with both rounding models were evaluated. Methods: An ASP was incorporated into existing teaching rounds for TS and disposition planning rounds for NTH. ASP-TS and ASP-NTH rounds both occurred once daily on weekdays with facetime of 3-4 hours per day for TS and 0.5-1 hour per day for NTH. Metrics included ASP recommendations and acceptance rates, total ASP time, ABX utilization, and clinical outcomes. Chi-squared and the Student's t-test were used as appropriate. Results: Between November 2016 to April 2017, ASPs reviewed 3184 NTH patients and 1322 TS patients. More opportunities for ASP intervention were identified with TS (40% vs. 26%, P < 0.001). Overall recommendation acceptance rates were higher for TS compared with NTH (95% vs. 79%, P < 0.001). Total recommendations identified per ASP-hour were higher for NTH vs. TS (1.76 vs. 0.93). ASP recommendations targeting ABX de-escalation, unnecessary use of fluoroquinolones, and treatment of asymptomatic bacteriuria were similar for both groups. Compared with baseline rates, ASP rounds were associated with a significant reduction (-6%, P = 0.01) in ABX days-of-therapy (DOT) for NTH but not for TS (-1%, P = 0.6). Anti-Pseudomonal (PSA) DOT significantly declined in both NTH (-11%, P = 0.04) and TS (-22%, P = 0.02). No significant changes in mortality, length of stay, and 30-day readmission rates were observed for either group. Conclusion: ASP rounds identified ample opportunities for improvement in ABX utilization in both NTH and TS models. Rounds were associated with a significant reduction in anti-PSA DOT for both models and a significant reduction in overall ABX DOT for NTH group. Although NTH provided a higher patient volume and allowed for more interventions per ASP-hour compared with the TS model, acceptance rates were lower, which may reflect a shorter amount of time spent on patient discussions. Disclosures: All authors: No reported disclosures.